Can a documentary increase help-seeking intentions in men? A randomised controlled trial. Issue 1 (3rd November 2017) - King, Kylie Elizabeth; Schlichthorst, Marisa; Spittal, Matthew J; Phelps, Andrea; Pirkis, Jane
Abstract : Background: We investigated whether a public health intervention—a three-part documentary called Man Up which explored the relationship between masculinity and mental health, well-being and suicidality—could increase men's intentions to seek help for personal and emotional problems. Methods: We recruited men aged 18 years or over who were not at risk of suicide to participate in a double-blind randomised controlled trial. Participants were randomly assigned (1:1) via computer randomisation to view Man Up (the intervention) or a control documentary. We hypothesised that 4 weeks after viewing Man Up participants would report higher levels of intention to seek help than those who viewed the control documentary. Our primary outcome was assessed using the General Help Seeking Questionnaire, and was analysed for all participants. The trial was registered with the Australian New Zealand Clinical Trials Registry (ACTRN12616001169437, Universal Trial Number: U1111-1186-1459) and was funded by the Movember Foundation. Results: Three hundred and fifty-four men were assessed for eligibility for the trial and randomised to view Man Up or the control documentary. Of these, 337 completed all stages (nine participants were lost to follow-up in the intervention group and eight in the control group). Linear regression analysis showed a significant increase in intentions to seek help in the intervention group, but not in the control group (coef.=2.06, 95% CI 0.48 to 3.63, P=0.01). Conclusions: Our trial demonstrates the potential for men's health outcomes to be positively impacted by novel, media-based public health interventions that focus on traditional masculinity. Trial registration number: ACTRN12616001169437, Results.